3d Magnetic Chains with an Asymmetrical Pyridyl-Triazole Ligand. Influence of Coordination and Local Distortion in the Ligand Field and Magnetometry - Venegas-Yazigi, D; Venegas-Yazigi, D (American Chemical Society, 2024)
Herein, we report the use of a simple N-donor asymmetrical Schiff base 1-(pyridin-2-yl)-N-(4H-1,2,4-triazol-4-yl)methanimine (L) as the main building block for the design of two new 1D 3d-coordination polymers (CPs), {[M(L)2(NCS)2]·2H2O}n (M = FeII for 1 and CoII for 2). Using FeII and CoII, the 1D structure is acquired using the N,N′-chelating iminopyridine coordination pocket of L and forming extended coordination bonds through the triazole fragments. 1 and 2, which are isostructural, presenting a zigzag chain topology with a strongly distorted MN6 environment around the metal cations. The 3D supramolecular structure of 1 and 2 is formed by S···H-O and N···H-O H-bonds of 1D zigzag chains and H2O guest molecules. Moreover, 1 and 2 are the first 3d-1D CPs based on the reported cation and ligand and one of the few compounds presenting the MN4(NCS)2 moiety in a 1D extended structure. Furthermore, a complete description of the electronic structure was done from an experimental and theoretical point of view. Weak antiferromagnetic interactions operating within the chains and local magnetic anisotropy were found and described in both compounds. In the case of 1, local anisotropy was modeled by a spin-only approach, leading to a positive D parameter expected for an octahedral-distorted FeII ion. Meanwhile, CoII ions in 2 present a strong axial distortion and a sizable rhombic contribution that induces a fast-magnetic relaxation at low temperatures. © 2024 American Chemical Society.